7.5k views
3 votes
(7x³-11x-1)-(12x³+x²-8)​

User Bdv
by
4.9k points

1 Answer

2 votes

Answer:


- 5 {x}^(3) - {x}^(2) - 11x + 7 \\

Explanation:

Before solving that we have to know that,


( + ) * ( + ) = ( + ) \\ ( - ) * (- ) = ( + ) \\ ( + ) * ( - ) = (- )

Let's solve now.


7 {x}^(3) - 11x - 1 - (12 {x}^(3) + {x}^(2) - 8) \\ 7 {x}^(3) - 11x - 1 - 12 {x}^(3) - {x}^(2) + 8 \\ 7 {x}^(3) - 12 {x}^(3) - {x}^(2) - 11x - 1 + 8 \\ = - 5 {x}^(3) - {x}^(2) - 11x + 7

Hope this helps you.

Let me know if you have any other questions :-):-)

User Scuttle
by
5.2k points